Risk Management Analysis and Business Development Strategies for Cage Aquaculture in Tomini Bay - Sastrawan, Uding; Kuntari, Wien; Warcito; Mulya, Muhammad Arif; Widodo, Bayu (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
Tomini Bay holds tremendous potential for the development of marine fish farming, particularly through the environmentally friendly and economically valuable Floating Net Cage (FNC) system. This study aims to analyze risk management and formulate development strategies for a fish farming business based on the Teaching Factory (TeFa) model at SMKN 1 Popayato, serving as an integrated vocational education model aligned with industry needs. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and questionnaires. The data were analyzed using SWOT analysis and a risk matrix. The results indicate that most identified risks fall into the moderate category, with one operational risk classified as high. Risk management strategies were implemented through mitigation and risk-sharing approaches, including competency-based training, human resource capacity building, partnerships with industry stakeholders, and adaptive cultivation practices in response to environmental changes. The study recommends enhancing human resource competencies and strengthening partnerships as key strategic actions to ensure the sustainability of the TeFa FNC business. These findings are expected to serve as a valuable reference for the development of productive vocational education units in the fisheries sector.